Implement Fuzzy-PID Controllers for Trajectory Tracking of an Underactuated Surface Vessel - Vo, Trung-Kien; Nguyen, Xuan-Dung; Ha, Manh-Tuan; Le, Trung-Kien (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Controlling of underactuated unmanned surface vessels (USVs) has been a research topic of interest in recent decades. However, control methods proposed in most studies have great complexity and are difficult to implement. This paper introduces guidance laws for the underactuated USV to track desire trajectories. Two control guidance laws will be established, which are the control of surge velocity and yaw angle. With the guidance laws, the controllers design process is simplified and easy to implement. PID controller is popular for its simplicity and ease of implementation. To maintain stability and reduce tracking error in various trajectories, a Fuzzy controller is introduced. The Fuzzy controller is designed to tune the gains of the PID controller. The Fuzzy-PID controller is designed for the USV to follow guidance laws, maintain stability and reduce tracking error. The proposed control method is implemented in simulations and experiments to verify its performance. The simulation and experiment show that this method can track different trajectories with small disturbances.